EUCLASE FROM THE NEAR-POLAR URALS (MALDYNYRD RANGE): NEW DATA - Kozyreva I.V.; Shvetsova I.V.; Yudovich Ya.E. (My University, 2004)
Our numerous findings of euclase in aporhyolite of the entire Al'kesvozh sequence, and gravelstones of the Tel'pos Formation clearly indicate that the Maldy rhyolites that greisenized in the Early Cambrian (?) served as a source of this mineral. The presence of euclase in genetically problematic aporhyolite diasporites testifies to the metasomatic origin of these convergent hydrolyzates Microinclusions in the euclase are characterized by a complex composition and crystallinity (both holocrystalline and aphanitic species are present), indicating a high rate of mineral ystallization from highly concentrated solutions during alteration of the Maldy rhyolites. This provides additional evidence for a hydrothermal rather than origin of disaporites and cognate hematite-supergene pyrophyllite schists.